2021
DOI: 10.51253/pafmj.v71i1.3315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patterns of Impacted Third Molars and Their Association With Vital Structures by Radiographic Examination

Abstract: Objective: To assess the patterns of impacted 3rd molars and their proximity with adjacent vital structures. Study Design: Comparative cross-sectional study. Place and Duration of Study: Oral & maxillofacial department of Rawalpindi Dental Hospital, from Oct 2016 toFeb 2018. Methodology: Patient sample size was 956. Orthopantomograms (OPGs) were assessed to determine the presence, patterns of impacted third molars and their relation to maxillary sinus and inferior alveolar canal (IAC) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
5
2
1
Order By: Relevance
“…In this study, based on Winter’s classification [ 20 ], mesio-angular was the most common type (54.9%) followed by vertical (23.4%), horizontal (16.8%), and disto-angular (4.9%). This was in agreement with Sedaghatfar et al [ 22 ], Gomes et al [ 23 ], Wassem et al [ 41 ], Quek et al [ 53 ], Deshpande et al [ 56 ], and Nyugen et al [ 57 ] In contrast, Kim et al [ 7 ] and Tantanapornkul et al [ 19 ] revealed that the horizontal angulation was the most common, followed by angular and vertical, whereas according to Chen et al [ 13 ], Bataineh et al [ 58 ], and Almendros-Marques et al [ 59 ], vertical impaction was the most common type. In this study, canal defects were most frequently seen with disto-angular impaction (82.4%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, based on Winter’s classification [ 20 ], mesio-angular was the most common type (54.9%) followed by vertical (23.4%), horizontal (16.8%), and disto-angular (4.9%). This was in agreement with Sedaghatfar et al [ 22 ], Gomes et al [ 23 ], Wassem et al [ 41 ], Quek et al [ 53 ], Deshpande et al [ 56 ], and Nyugen et al [ 57 ] In contrast, Kim et al [ 7 ] and Tantanapornkul et al [ 19 ] revealed that the horizontal angulation was the most common, followed by angular and vertical, whereas according to Chen et al [ 13 ], Bataineh et al [ 58 ], and Almendros-Marques et al [ 59 ], vertical impaction was the most common type. In this study, canal defects were most frequently seen with disto-angular impaction (82.4%).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, 104 (29.7%) of the mandibular third molars showed cortication whereas 246 cases (70.3%) showed an absence of cortication. The percentage of absence of cortication in the present study was far greater than that noted by Kim et al [ 7 ] Pandey et al [ 30 ], and Waseem et al [ 41 ], where in 61%, 63.8%, and 53.9% of CBCT images respectively, the IAN was actually in contact with the root of third molar. With respect to the OPG signs, diversion of canal showed the highest number of cases with absence of cortication between the third molar and IAC in CBCT images.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The distribution of IMTM in our study indicated a higher prevalence among younger age groups, with the majority (30.33%) observed in subjects aged 18-30 years. These findings align with previous studies conducted by various authors [28,29]. Furthermore, authors observed a higher proportion of SRIMTM cases among females, which can be explained by Hellman's theory [29].…”
Section: Discussionsupporting
confidence: 92%
“…These findings align with previous studies conducted by various authors [28,29]. Furthermore, authors observed a higher proportion of SRIMTM cases among females, which can be explained by Hellman's theory [29]. According to this theory, female jaw growth ceases when the third molars begin to erupt, whereas in males, jaw growth continues beyond the eruption time, resulting in a lower incidence of IMTM in males compared to females.…”
Section: Discussionsupporting
confidence: 90%